1984
DOI: 10.2170/jjphysiol.34.167
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory influence of amino acids on Secretagogues induced exocrine secretion in isolated perfused rat pancreas.

Abstract: Influence of amino acids upon pancreatic exocrine secretion has been investigated in the isolated perfused pancreas of rats. Arg produced significant and dose-related inhibition of pancreatic juice flow, protein output and amylase output evoked by CCK-PZ (1.25 pM). The secretory response evoked by CCK-PZ was inhibited by other amino acids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…In the present study, fresh primary pancreatic acinar cells were used to study effects of leucine dosages on amylase release. The results obtained here shows that leucine inhibits release of α-amylase, which differs from results observed in in vivo ruminant experiments, but similar with the results investigated in isolated perfused rat pancreas [7]. Leucine inhibited the α-amylase release in primary pancreatic acinar cells, and when concentration of leucine increased from 0 to 1.35 mM, the α-amylase release was decreased by 73%.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, fresh primary pancreatic acinar cells were used to study effects of leucine dosages on amylase release. The results obtained here shows that leucine inhibits release of α-amylase, which differs from results observed in in vivo ruminant experiments, but similar with the results investigated in isolated perfused rat pancreas [7]. Leucine inhibited the α-amylase release in primary pancreatic acinar cells, and when concentration of leucine increased from 0 to 1.35 mM, the α-amylase release was decreased by 73%.…”
Section: Discussionsupporting
confidence: 88%
“…Leucine not only serves as substrates for protein synthesis but also participates in regulation of some physiological processes. In isolated perfused rat pancreas, leucine infusion could inhibit the secretion of pancreatic enzymes [7]. However, it was reported that duodenum infusion of leucine could increase secretion of pancreatic α-amylase in dairy goat [5] and Holstein cow [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same phenomenon has previously been described by Harada et al ~4 They demonstrated that arginine dose-dependently inhibited stimulated protein release from the isolated perfused rat pancreas. Since exogenous hormones did not produce the same effect, Harada et al considered it unlikely that this inhibitory effect was mediated by pancreatic hormones, but they did not measure hormone secretion in their study 24. While we were able to confirm their finding that …”
Section: Discussionsupporting
confidence: 43%